Tantangan Regulasi Pajak dalam Ekonomi Digital di Indonesia: (Kasus Transaksi E-Commerce) - Desy Marisi Josephine; Sylvia Fettry Elvira Maratno (AKUNTANSI 45, 2026)
This study aims to analyze the challenges of tax regulations in Indonesia's digital economy, focusing on e-commerce transactions. The method used is a descriptive qualitative approach with literature review techniques. Secondary data was obtained from scientific journals, official government reports, and relevant laws and regulations. The results indicate that the value of Indonesian e-commerce transactions will reach IDR 487 trillion by 2024, with a cumulative growth of 137% over the past five years. However, 84.21% of digital transactions take place outside formal marketplace platforms, making them difficult for tax authorities to monitor. The main challenges identified include: (1) difficulty monitoring cross-platform digital transactions; (2) low tax compliance among digital MSMEs, with more than 900,000 taxpayers failing to meet their tax obligations; (3) cross-border tax jurisdiction issues; and (4) limited capacity of technology-based oversight systems. This study concludes that adaptive tax policies, expansion of the tax collection system through digital platforms, increased tax literacy, and strengthening of technology-based oversight systems are needed to enhance the effectiveness of tax regulations in Indonesia's digital economy.